Alternative mixing strategy for biodiesel production: mixed flow impeller characterization - Mohiuddin, A. K. M.; Adeyemi, Nabeel A. (IIUM Press, 2011)
A mixed 110\\ impeller has heen used as an alternative mixing strategy for hiodiesel production. in order to comhine salient hydrodynamic features and overcome stagnation during mixing. This unique comhined radial and axial flow is presented is to show the advantage of this impeller. The numerical simulation of this impeller was carried out using the Reynolds stress model (RS\I) and results compared well with experimental PlY data forthe velocity lield at bottom of the vessel for mean. radial and axial velocity than for the surface. Although the RS\I was used at a higher computational cost. associated power number and energy of the impeller was also ohserved to he helter predicted.